2002
DOI: 10.1892/0891-6640(2002)016<0533:gapcop>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic and Phenotypic Characterization of Clostridium perfringens and Clostridium difficile in Diarrheic and Healthy Dogs

Abstract: The objectives of this study were to examine the potential roles of Clostridium difficile and enterotoxigenic Clostridium perfringens in diarrhea in dogs by comparison of isolation, determination of toxin status via enzyme-linked immunosorbent assay (ELISA), and application of multiplex polymerase chain reaction (PCR). These techniques were used to evaluate fecal specimens in 132 healthy and diarrheic dogs. These dogs were prospectively evaluated by grouping them into the following 3 categories: hospitalized d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
97
4

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(108 citation statements)
references
References 45 publications
7
97
4
Order By: Relevance
“…In addition, all animal and human isolates displayed 39-bp deletions in tcdC, and most (45/47; 96%) were binary toxin positive. Although C. diffi cile is recognized as a cause of disease in several animal species (19)(20)(21)(22), little investigation has been conducted on the potential for interspecies transmission of C. diffi cile to humans. Previous studies have suggested the possibility of C. diffi cile transmission between humans and domestic pets (23,24), but no interspecies transmission has been documented, and few studies have examined the possible link between CDAD in food animals and humans.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, all animal and human isolates displayed 39-bp deletions in tcdC, and most (45/47; 96%) were binary toxin positive. Although C. diffi cile is recognized as a cause of disease in several animal species (19)(20)(21)(22), little investigation has been conducted on the potential for interspecies transmission of C. diffi cile to humans. Previous studies have suggested the possibility of C. diffi cile transmission between humans and domestic pets (23,24), but no interspecies transmission has been documented, and few studies have examined the possible link between CDAD in food animals and humans.…”
Section: Discussionmentioning
confidence: 99%
“…For example, one study showed the presence of cpe-positive type A isolates and CPE in the small intestines of a goat kid suffering from necrotic enteritis (199). Additionally, fecal CPE and CPE-positive fecal isolates have been associated with canine diarrhea (200), and cpe-positive strains were suggested to cause recurrent diarrhea in dogs. In horses, fecal CPE was detected in Ïł20% of adults with diarrhea and Ïł30% of foals with diarrhea, while no fecal CPE was detected in healthy adult horses or foals (201).…”
Section: Diseases Involving Primarily Plasmid-encoded Toxinsmentioning
confidence: 99%
“…However, C. perfringens can be cultured from the fecal specimens of more than 80% of diarrheic and nondiarrheic dogs, and CPE can also be detected in up to 14% of nondiarrheic, healthy dogs 11, 1515, 16, 17.…”
mentioning
confidence: 99%
“…However, C. perfringens can be cultured from the fecal specimens of more than 80% of diarrheic and nondiarrheic dogs, and CPE can also be detected in up to 14% of nondiarrheic, healthy dogs 11, 1515, 16, 17. In addition, the moderate‐to‐poor sensitivity and specificity of commercial ELISA, which was used in this previous study, have been reported by comparison with the gold standard of cytotoxicity assays 18…”
mentioning
confidence: 99%